THE ANALYSIS OF WOMEN’S ATTITUDES TOWARDS GENDER DISCRIMINATION IN “7 HATI 7 WANITA 7 CINTA” MOVIE - Lisa Purwanti; I Wy Dirgeyasa; Elisa Betty Manullang (LINGUISTICA, 2018)
The research was focused on the topic about Women’s attitudes toward gender discrimination they face in the movie with title ‘7 Hati 7 Cinta 7 Wanita’. This study was aimed at identify the kinds of gender discrimination faced in the movie and the attitudes of women towards gender discrimination they face in the movie. This study was conducted by applying descriptive qualitative method. The source of data was taken from 7 Hati 7 Cinta 7 Wanita (2010) script movie. The data are collected by using documentary technique. Instrument for collecting the data is using documentary sheet. The technique for analyzing the data is descriptive qualitative research. The results of this research was types of genders discriminatio can found in the movie are Marginalization, Subordination, Stereotype, Violence and Workload. The women’s attitudes toward five kinds of gender discrimination they face are different based on the type of attitudes, they are Cognitive responses, Affective responses and Conative responses.Keywords: Gender Discrimination, Attitudes, Movie.